Mycorrhizal symbioses and tree diversity in global forest communities - Jiang, Feng; Pu, Xucai; Schmid, Bernhard; Reich, Peter B; Liang, Jingjing; Abbasi, Akane O; Aguirre-Gutiérrez, Jesús; Zambrano, Angelica Maria Almeyda; Altman, Jan; Álvarez-González, Juan Gabriel; Alves, Luciana F; Amani, Bienvenu H K; et al. (Science advances, 2025)
Unraveling the mechanisms underlying the maintenance of species diversity is a central pursuit in ecology. It has been hypothesized that ectomycorrhizal (EcM) in contrast to arbuscular mycorrhizal fungi can reduce tree species diversity in local communities, which remains to be tested at the global scale. To address this gap, we analyzed global forest inventory data and revealed that the relationship between tree species richness and EcM tree proportion varied along environmental gradients. Specifically, the relationship is more negative at low latitudes and in moist conditions but is unimodal at high latitudes and in arid conditions. The negative association of EcM tree proportion on species diversity at low latitudes and in humid conditions is likely due to more negative plant-soil microbial interactions in these regions. These findings extend our knowledge on the mechanisms shaping global patterns in plant species diversity from a belowground view.
Keywords: Biodiversity; Symbiosis; Soil Microbiology; Mycorrhizae; mykorhiza; půdní mikrobiologie; stromy; symbióza; Trees; lesy; biodiverzita; Forests